Genetic correlations in the rhesus macaque dentition. Issue 148 (November 2020) - Hardin, Anna M.
Abstract: Quantitative genetic analyses can indicate how complex traits respond to natural selection by demonstrating the genetic relationships between features that constrain their evolution. Genetic correlations between dental measurements have been estimated previously in baboons, humans, and tamarins and indicate variable patterns of modularity by tooth type across these taxa. Here, heritabilities of, and genetic correlations between, linear dental measurements were estimated from the Cayo Santiago rhesus macaques ( Macaca mulatta ). Relationships between the genetic correlation matrix and matrices designed to test hypotheses of modularity by tooth type, region, function, and development were assessed using a random skewers approach. Dental measurements were found to be moderately to highly heritable, with 24 of 28 heritability estimates differing significantly ( p < 0.05) from zero. Almost all genetic correlations between dental dimensions were positive. The genetic correlation matrix was most similar to a regionally modular matrix, with distinct anterior and postcanine tooth modules. This pattern is consistent with previous quantitative genetic analyses of baboons and previous phenotypic analyses of cercopithecoid primates. The existence of a genetic module for the canines and honing premolar was not supported. Ongoing selection pressures, rather than strong genetic constraints, are likely necessary to preserve functional relationships between the canines and honing premolar based on these findings. The genetic correlation matrix of the Cayo Santiago rhesus macaques mirrors patterns of phenotypic correlations observed for cercopithecoid primates broadly and demonstrates that genetic contributions to these patterns may be fairly stable over the course of cercopithecoid evolution. The quantitative genetic study of additional taxa will be necessary to determine whether the regional modularity of baboons and macaques, or the integrated pattern of humans and tamarins, is shared more broadly across primates.